Penerapan Arsitektur MVP dalam Pengembangan Aplikasi Pemesanan Tiket Seminar Berbasis Android - I Made Sukarsa; I Nyoman Piarsa; I Gede Bagus Premana Putra (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The success of an event, especially a seminar cannot be separated from the success of the organizer to get participants. The scattered challenges faced by the seminar organizers are closely related to the ease and convenience of the procedures applied to order seminar tickets to prospective participants. So that the application of information and communication technology is needed by the organizer as a tool to provide convenience and comfort to prospective participants. Ticket reservations are generally done manually and still use tickets in printed. An application is needed to speed up and simplify the ticket booking process for prospective participants. To solve this problem, prospective seminar participants will use the seminar ticket booking application via a smartphone device. This application uses the RESTful API on the Laravel framework, as one of the implementations of web service. Security of data exchange between android devices and web services using Laravel Passport, as a token generator API. The architecture that is applied in the development of android applications is the MVP architecture (Model, View, Presenter). Using QR-codes on tickets and sending tickets via e-mail participants can also avoid the possibility of loss and damage to tickets obtained by participants.